Driving sustainability in Indonesia: the importance of corporate citizenship in realizing sustainable development goals - Arif Rahman Hakim; Nurul Asfiah (Mednarodno Inovativno Poslovanje, 2024)
Purpose of the article – Corporate Citizenship (CC) and Sustainable Development Goals (SDGs) are two interrelated and essential concepts to achieve sustainable development by 2030. This topic is particularly interesting and relevant today, where companies are expected to pursue profits and contribute to social and environmental well-being. This study aims to describe the implementation practices of corporate citizenship in supporting the achievement of the Sustainability Development Goals of companies in Indonesia.